Android App-hook and plug-in technology - Bao, Jianqiang (Boca Raton, FL : CRC Press, 2020)
This book presents the Android plug-in technology used in Android development. This technology is widely used by a majority of Chinese internet companies, and is becoming more widely used worldwide. The book fully describes the history of Android plug-in technology, the installation and startup process, and new features of the Android plug-in technology. It also explores plug-in solutions for peripheral technologies. The book is designed to help Android app developers better understand the underlying technology of the Android system. Features Introduces Android system knowledge, including the communication between AMS and four components Describes the Hook technique by Proxy.newProxyInstance and reflection, to modify Android system behavior, for example, to launch an activity not declared in the AndroidManifest. Shows how to use the Hook apk packaging process in Gradle Covers how to merge the resources in the plugin app and the host app, and how to merge dex of the host app and all the plugin apps Presents the SO technique and how to launch SO files dynamically
3.1.1 Get the Class Using a String3.1.1.1 Get the Class Using a String; 3.1.1.2 Class.forName; 3.1.1.3 Property class; 3.1.1.4 Property TYPE; 3.1.2 Get the Property and Method of the Class; 3.1.2.1 Get the Constructor of the Class; 3.1.2.2 Invoke a Private Method of the Class; 3.1.2.3 Invoke a Private and Static Method of the Class; 3.1.2.4 Get a Private Field of the Class and Modify Its Value; 3.1.2.5 Get the Private Static Field of the Class and Modify Its Value; 3.1.3 Generics and Singleton; 3.2 jOOR; 3.2.1 Get a Class from a String; 3.2.1.1 Get a Class from a String
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Android (Electronic resource); Application software -- Development; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Networking / General; COMPUTERS / Internet / General